A Rare Observation of Endoscopic Transluminal Drainage of Pancreatogenic Destruction Areas in Infected Necrotizing Pancreatitis - A. Ch. Askerov; Yu. D. Kulikov; Y. S. Teterin; K. T. Agakhanova; E. S. Yeletskaya; P. A. Yartsev (Неотложная медицинская помощь)
Necrotizing forms of acute pancreatitis, as the most severe in terms of prognosis, occur in 25–30% of cases with a mortality rate of 27–32%, while in most cases these are adults of working age, which emphasizes the social significance of this problem. This article presents a rare observation of endoscopic intraluminal drainage of zones of pancreatogenic destruction in severe necrotizing pancreatitis. The multidisciplinary individual approach we have chosen makes it possible to treat this group of patients most effectively, which confirms the presented clinical observation.